Hybrid Self‐Assembling Peptide/Gelatin Methacrylate (GelMA) Bioink Blend for Improved Bioprintability and Primary Myoblast Response. Issue 2 (1st December 2021) - Boyd-Moss, Mitchell; Firipis, Kate; Quigley, Anita; Rifai, Aaqil; Cichocki, Artur; Whitty, Sarah; Ngan, Catherine; Dekiwadia, Chaitali; Long, Benjamin; Nisbet, David R.; Kapsa, Robert; Williams, Richard J.
Abstract : Organ fabrication as the solution to renewable donor demands requires the ability to spatially deposit viable cells into biologically relevant constructs; necessitating reliable and effective cell deposition through bioprinting and the subsequent ability to mature. However, effective bioink development demands advances in both printability and control of cellular response. Effective bioinks are designed to retain shape fidelity, influence cellular behavior, having bioactive morphologies stiffness and highly hydrated environment. Hybrid hydrogels are promising candidates as they reduce the need to re‐engineer materials for tissue‐specific properties, with each component offering beneficial properties. Herein, a multicomponent bioink is developed whereby gelatin methacrylate (GelMA) and fluorenylmethoxycarbonyprotected self‐assembling peptides (Fmoc‐SAPs) undergo coassembly to yield a tuneable bioink. This study shows that the reported fibronectin‐inspired fmoc‐SAPs present cell attachment epitopes RGD and PHSRN in the form of bioactive nanofibers; and that the GelMA enables superior printability, stability in media, and controlled mechanical properties. Importantly, when in the hybrid format, no disruption to either the methacrylate crosslinking of GelMA, or self‐assembled peptide fibril formation is observed. Finally, studies with primary myoblasts show over 98% viability at 72 h and differentiation into fused myotubes at one and two weeks demonstrate the utility of the material as a functional bioink for muscle engineering. Abstract : In this work, muscle tissue is 3D‐bioprinted with a novel bioink formulation. The bioink presents fibrous bioactive properties of the body's native scaffold, while also improving biofabrication outcomes. Self‐assembling peptides are combined with GelMA creating a hybrid bioink. This work sets the stage for future hybrid bioinks for muscle biofabrication.